Excellent Nanofiber Adhesion for Hybrid Polymer Materials with High Toughness Based on Matrix Interdiffusion During Chemical Conversion. (13th December 2018) - Daelemans, Lode; Van Paepegem, Wim; D'hooge, Dagmar R.; De Clerck, Karen
Abstract: One of the challenges for multiphase materials is the improvement of the interconnectivity of their separate phases. A promising route toward excellent adhesion is molecular interdiffusion, in which molecules are transferred to enable physical interaction. In the present work, a novel straightforward and direct method is developed to tune the adhesion between electrospun nanofibers and their matrix, starting from fundamental insights on molecular diffusion and considering in situ chemical formation of one of the polymer phases to effectively regulate interdiffusion. Proof‐of‐concept is provided for the adhesion of a thermoplastic phase (poly(ε‐caprolactone)) to a thermoset matrix (epoxy) during the cured‐induced formation of the latter. For isothermal curing, only an intermediate temperature (50 °C) allows the production of nanofiber hybrid materials with good adhesion between the constituents and preservation of the nanomorphology. Moreover, excellent adhesion properties are obtained in case a two‐step curing (25 °C/80 °C), or coaxial electrospinning (polyamide 6/poly(ε‐caprolactone)) toward core–shell nanomorphologies is applied. Improvements in toughness of the optimized interdiffused materials with G values over 600 J m −2 (up to 65% improvement) are recorded due to excellent bonding of the thermoplastic nanofibers with the matrix. Abstract : A direct route that controls interfacial bonding between two polymeric materials is proposed, with molecular diffusion, i.e., interdiffusion, during in situ chemical formation of one of those materials. The route increases the toughness of nanofibrous hybrid materials with G values over 600 J m −2 (up to 65% improvement) for optimally designed curing temperature history and fiber morphology, including core–shell configurations.